Determinants of Technology Adoption in Mexico - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2013)
The author tries to identify the impact of firm-, region-, and industry-specific characteristics on technology adoption by Mexican firms. Cross-sectional and panel data from 1992-99 show that the firms most likely to adopt new technology are large, train workers, have highly skilled workers, are near the U.S. border, and are owned by foreign entities. Also, bigger firms, firms with a large share of highly skilled workers, and firms that train workers, use intensively more complex technologies in their production process.